MEMBANGUN USAHA KREATIF, INOVATIF, DAN BERMANFAAT MELALUI PENERAPAN KEWIRAUSAHAAN SOSIAL PADA UMKM SATYAGRAHA DI KABUPATEN GIANYAR - I Kadek Widiantara; Wisnu Ardiansyah; Ni Putu Yuli Tresna Dewi (Nusantara Hasana Journal, 2023)
Entrepreneurship can be in the form of imaginative and inventive capacities, keen to see gaps and remain open to any input and positive changes that can bring trade to continue to grow and have self-respect. The purpose of this study was to determine the effect of creativity, innovation that is beneficial to the entrepreneurship of UMKM Sukla Satyagraha. One of the pioneers of MSME development in Bali is the Satyagraha Movement. The Satyagraha Movement is a culinary business movement as well as traders with micro and medium enterprises which is a form of culinary or business preservation in Bali that uses the concept of Hinduism as well as synergizes between ancestral concepts and the concept of modern generations that have undergone various forms of change. Being an innovator was carried out by respondents, although currently many sell klepon, Yadnya decorations and clothing and fiber trays with a similar concept, the Klepon Legend Gianyar brand has already been known to the market as a Klepon seller whose taste makes customers addicted. Ibu Dayu's Klepon is known as the most delicious Klepon in the world by using basic ingredients from glutinous rice flour and Mr. Wayan's decoration shop which has a variety of decorations and clothing compared to other fashion shop owners. In addition, in this case, businesses that offer goods that follow this comparison concept cannot be considered progress, because they are considered to be imitating or adapting existing goods to the same storefront. Trade owners also arrange creative strategies to overcome the problem of changing culinary patterns. Culinary patterns alone can lead to switching clients and spoiled item offerings.